The role of qualitative research methods in understanding management control systems - Hared, Bashir Abdisamad; Abdullah, Zarifah; Rafiul Huque, Sheikh Mohammed (2013)
To understand a socially-constructed management control systems (MCS) requires an in-depth study of daily habits, routines and processes that takes place in the organizational operations.It is obvious that such behavioral aspects of organizations’ operations might not be captured through the prevailing conventional quantitative (positivist) research strategies. The current conventional (positivist) research approaches failed to provide adequate information of the socially constructed phenomena such as MCS.Thus, to cope with the specific social phenomenon, qualitative research approaches is deemed to be the most appropriate device that does not only penetrate into the organizations’ social aspects, but also facilitates to genuinely explore the subjective meanings that associates with the specific MCS forms that is constructed by the sociocultural factors of the respective society. Qualitative research approaches may offer wealthy information about the MCS phenomenon in its social settings. Drawing upon the role of qualitative research methods, in constructing meaningful relationships between MCS theory and practices, this paper attempts to enrich the descriptions and explanations regarding the critical issues that justify the use of qualitative research strategies, particularly MCS imbedded in its social contexts.